2022
DOI: 10.1007/s11356-022-19578-0
|View full text |Cite
|
Sign up to set email alerts
|

Designing an optimization model for green closed-loop supply chain network of heavy tire by considering economic pricing under uncertainty

Abstract: The conditions of global competition and environmental sensitivities have made organizations and factories to collect returned products. In such a way that these organizations have tried rehabilitate, recycle or destroy these products in order to protect the environment. This paper propose a mathematical model for the green closed-loop supply chain network of heavy tire by considering the economic pricing of its products under conditions of uncertainty, which economically determines the price and leads to more… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…They argued that environmental detrimental impacts are directly related to the size of demand but inversely related to the responsiveness level. Amirian et al (2022) formulated a bi-objective fuzzy model for developing a green CLSC in the heavy tire industry. For this purpose, they utilized the economic pricing concept.…”
Section: Introductionmentioning
confidence: 99%
“…They argued that environmental detrimental impacts are directly related to the size of demand but inversely related to the responsiveness level. Amirian et al (2022) formulated a bi-objective fuzzy model for developing a green CLSC in the heavy tire industry. For this purpose, they utilized the economic pricing concept.…”
Section: Introductionmentioning
confidence: 99%
“…The authors in (Mondal and Giri 2020a ) studied a multi-period CLSC model including a single manufacturer as well as a retailer to investigate the effects of marketing, product collection, and green innovation on supply chain decisions. Amirian et al ( 2022 ) suggested a mathematical model in a heavy tires CLSC by examining the economic price of its goods under unpredictable situations.…”
Section: Literature Reviewmentioning
confidence: 99%